Salinity changes impact of hazardous chemicals in Enchytraeus albidus - Patrício Silva, Ana L.
Supralittoral ecosystems are among the most challenging environments for soil organisms, particularly when salinity fluctuations are involved, frequently combined with the presence of contaminants as a result of intense anthropogenic activities. Knowledge of how salinity influences the effect of contaminants in supralittoral species is crucial for determining the safety factors required when extrapolating results from optimal laboratory conditions to these natural ecosystems. The present study therefore evaluated the effects of 2 metals (copper and cadmium) and 2 organic compounds (carbendazim and 4-nonylphenol) in the absence or presence of 15‰ NaCl in the potworm Enchytraeus albidus, a model organism for ecotoxicology studies commonly found in supralittoral ecosystems, The potworms had a higher reproduction in saline soil than in control soil. Moreover, the effects of copper and carbendazim on reproduction were smaller than when they were tested in nonsaline soil. Potworms exposed to nonsaline soils also had significantly higher tissue concentrations of metals, which partly explains the effects on reproduction. The influence of salinity on effects of 4-nonylphenol was, however, less clear; effects on survival decreased in saline soil, but effects on reproduction were highest in saline soil. The latter slightly correlated with tissue concentrations of the chemical. The present study provides the first evidence that soil salinity has a significant influence on the impact of contaminants evaluated with the enchytraeid reproduction test.